THE APPLICATION OF THE PRINCIPLE OF BALANCE IN LEGAL PROTECTION OF THE IMPLEMENTATION OF WORK AGREEMENTS: THE MECHANISM OF WORK AGREEMENTS IN AUTOMOTIVE SECTOR COMPANIES IN INDONESIA - BUDIMAN, ANWAR (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
This labor problem is quite complex especially in terms of implementing work agreements. Work agreements made between employers and workers prone to conflict, especially if there are problems with Termination of Employment, wages and conflicts of interest. The arrangement of the work agreement itself is contained in Article 56 up to Article 66 of Act Number 13 of 2003 concerning Employment but for the author the provision is still imperfect considering the format of the work agreement itself is not clearly regulated even though this provision is very important to protect workers' rights. Based on this, the author raised the contents of this study around the issue of work agreements and supervision of the implementation of work agreements, especially Unspecified Time Work Agreements and Specific Time Work Agreements. According to Article 1 number 14 of Act Number 13 of 2003 concerning Manpower (